Adverse effects of in vitro GenX exposure on rat thyroid cell viability, DNA integrity and thyroid-related genes expression. (September 2020) - Coperchini, Francesca; Croce, Laura; Denegri, Marco; Pignatti, Patrizia; Agozzino, Manuela; Netti, Giuseppe Stefano; Imbriani, Marcello; Rotondi, Mario; Chiovato, Luca
Abstract: The hexafluoropropylene-oxide-dimer-acid (GenX) is a short-chain perfluoroalkyl substance that was recently introduced following the phase out of PFOA, as an alternative for the process of polymerization. GenX was detected at high concentrations in rivers, drinking water and in sera of exposed workers and recent findings suggested its potential dangerousness for human health. Aim of the study was to assess the consequences of GenX exposure on in vitro thyroid cells with particular attention to the effects on cell-viability, proliferation, DNA-damage and in the thyroid-related genes expression. FRTL-5 rat-thyroid cell line were incubated with increasing concentrations of GenX for 24 h, 48 h and 72 h to assess cell viability by WST-1. DNA-damage was assessed by comet assay and further confirmed by micronucleus assay. The proliferation of survived cells was measured by staining with crystal violet and evaluation of its optical density after incubation with SDS. Changes in TTF-1, Pax8, Tg, TSH-R, NIS and TPO genes expression were evaluated by RT-PCR. GenX exposure reduced FRTL-5 viability in a time and dose-dependent manner (24 h: ANOVA F = 22.286; p < 0.001; 48 h: F = 43.253, p < 0.001; 72 h: F = 49.708, p < 0.001). Moreover, GenX exerted a genotoxic effect, as assessed by comet assay (significant increase in tail-length, olive-tail-moment and percentage of tail-DNA) and micronucleus assay, both at cytotoxic and non-cytotoxic concentrations. Exposure to GenX at concentrations non-cytotoxic exerted a significant lowering of the expression of the regulatory gene TTF-1 (p < 0.05 versus untreated) and higher expression of Pax-8 (p < 0.05 versus untreated) and a down-regulation of NIS (p < 0.05 versus untreated). In addition, cells survived to GenX exposure showed a reduced re-proliferation ability (24 h: ANOVA F = 11, 941; p < 0, 001; 48 h: F = 93.11; p < 0.001; 72 h F = 21.65; p < 0.001). The exposure to GenX produces several toxic effects on thyroid cells in vitro. GenX is able to promote DNA-damage and to affect the expression of thyroid transcription-factor genes. Graphical abstract: Image 1 Highlights: GenX exposure reduces rat thyroid cells viability. GenX exposure exerts genotoxicity as assessed by comet and micronucleus assays. GenX exposure modifies the expression of some thyroid transcription factors genes. GenX exposure reduces FRTL-5 cells ability to proliferate. GenX exposure is potentially dangerous for thyroid cells. Abstract : Capsule: GenX exposure of FRTL-5 at concentrations found in exposed workers reduced cell viability and proliferation, induced genotoxicity and altered gene expression.